PERLINDUNGAN HUKUM BAGI TERSANGKA PIDANA PAJAK DI PRAPERADILAN DITINJAU DARI PUTUSAN NO.PUT MK 21/PUU-XII/2014 - Vonnicia Vonnicia; Nanda Dwi Rizkia; Hardi Fardiansyah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Juridically, crimes in the field of taxation show that these crimes are the substance of tax law because the rules of tax law are violated. Sociologically, crimes in the field of taxation have shown a real situation that occurs in society as a form of activity by tax officials, taxpayers, tax officials or other parties. In the Constitutional Court Decision, it was decided that the provisions of Article 77 letter A of the Criminal Procedure Code do not have binding legal force as long as they are not interpreted including the determination of suspects, searches and confiscations. As for one of the legal considerations, the determination of a suspect is part of the investigative process which is a deprivation of human rights, so the determination of a suspect by an investigator should be an object that can be requested for protection through pretrial legal endeavors. This is solely to protect a person from the arbitrary actions of an investigator which is most likely to occur when a person is named a suspect, even though in the process it turns out that there was an error, so there are no institutions other than pretrial institutions that can examine and decide them. The research method used is normative juridical, the approach method is more emphasis on law, the source of legal material is law, and the type of collection of legal material is by literature study. The results of this study are that the Constitutional Court's decision provides protection for someone who has experienced an erroneous legal process when he is named a suspect. In the provisions of Article 8 of Law 39/1999 concerning Human Rights it is regulated that "The protection, promotion, enforcement and fulfillment of human rights is primarily the responsibility of the government. This means that the Constitutional Court takes a role in fulfilling human rights through its decisions as part of constitutional responsive efforts. One element of legal protection that is emphasized through this decision is legal certainty that investigators must carry out investigative actions in accordance with applicable legal procedures